Anterior vaulting of single piece in-the-bag intraocular lens after blunt trauma - Seung Hoon Oh; Jae Young Park; Hye Bin Yim; Na Young Lee (Journal of Optometry, 2012)
A 64-year-old man complained of difficulty with far vision in the right eye after blunt trauma by his hand during sleep. He had undergone uneventful phacoemulsification and intraocular lens (IOL) implantation of both eyes one week before the event. On slit lamp examination, the anterior chamber was shallow compared to postoperative one day or the left eye. After mydriasis, IOL position was perfect, within the capsulorrhexis margin, and no haptics were protruded. SE of his right eye was −4.00 diopter after trauma, although spherical equivalent (SE) of both eyes was near emmetropia one day after cataract surgery. We decided on IOL reposition or exchange. Intraoperatively, we pushed the IOL posteriorly; the IOL was vaulted posteriorly, as expected. After surgery, his SE was +0.25 with the same diopter IOL. We report the case on the possibility of 4-point haptic IOL vaulting anteriorly by blunt trauma within the capsular bag.